Recovering Knowledge Commons for the Global South (Journal of the Digital Humanities Association of Southern Africa, 2024)
The colonial encounter instituted the hegemony of documentary practices over oral, performative and manuscript practices. Only knowledge validated through the process of print publication could stand the test of legal scrutiny. On the one hand the Western epistemological quest glossed over ideas that existed through ephemera, on the other hand that knowledge which Western print practices imbibed from non-European traditions were henceforth, locked behind intellectual property regimes and restrictive archival practices. This tremendously skewed access to knowledge between the North and the South. Tools for digital transformation, particularly those that are based on artificial intelligence (AI) and machine learning (ML), can be culture specific e.g. training data for Optical  Character Recognition (OCR)/ Hand-written Text Recognition (HTR); datasets for natural language processing. In the absence of culture specific tools in underdeveloped societies Anglo-American interpretive categories and assumptions become the default. Further, Anglo-American institutions work to use their advantage in the balance of knowledge distribution to maintain their hegemonic position. In order to protect the South’s access to human heritage and knowledge we need to develop technologies that leverage the potentials of digital communication for increased conversations among languages of the South.
Keywords: Digital Transformation; Low-resource Languages; Global South; Natural Language Processing; Typography